At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer: i = -1
Explanation:
First get the variable by itself. To do that, add six to both sides of the equation. You will have -6 = 6i. Than divide both sides by 6. It will give you i = -1.
Explanation:
First get the variable by itself. To do that, add six to both sides of the equation. You will have -6 = 6i. Than divide both sides by 6. It will give you i = -1.
-12 = 6i - 6
-12 + 6 = 6i - 6 + 6
-12 + 6 = 6i
(-12 + 6)/6 = (6i)/6
(-12 + 6)/6 = i
i = (-12 + 6)/6
-12 + 6 = 6i - 6 + 6
-12 + 6 = 6i
(-12 + 6)/6 = (6i)/6
(-12 + 6)/6 = i
i = (-12 + 6)/6
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.